The Linkage Between Inflammation and Immune Tolerance: Interfering with Inflammation in Cancer - Stanislavovich Rogovskii, Vladimir (Current Cancer Drug Targets, 2017)
Background: It is widely accepted that chronic inflammation critically contributes to cancer. Immune tolerance in cancer mediates tumor escape from the immune system. The mechanisms of relations between inflammation and immune tolerance are still not fully elucidated. Objective: The main mechanisms that link inflammation and tolerance are considered. Drug targets that are in use to interfere with inflammation in cancer are discussed. Conclusion: Inflammation mediates tumor-induced tolerance. The induction and the maintenance of the chronic inflammatory response is a universal mechanism of immune tolerance.
Keywords: resolution